Structural performances and fire resisting ability of rubberized concrete wall panel utilizing gypsum board as the skin layer - Chew, Kai Yuan (2022)
Disposal of waste tires is getting severe over the past century as recycling the waste tires is not a common practice. Rubber aggregates produced from waste tires could be used to replace mineral aggregates in concrete wall panels due to their lower unit weight. Such replacement is environmentally sustainable and cost-effective in construction. This study aims to investigate the fire resistance, and structural and thermal performance of the sized-down sandwiched rubberized lightweight foamed concrete (RLFC) wall panel with varying thicknesses of RLFC cores and gypsum board skin layer by conducting flame exposure, thermal conductivity, load bearing, and flexural tests. The gypsum board is used to serve as the sandwiched RLFC wall panel's sheathing material, while the RLFC core with a density of 1150 kg/m3 is produced to serve as the inner core. The gypsum boards are primarily used to sustain extreme heat while the RLFC core is mainly responsible for supporting the structural load. Epoxy resin is chosen as the connector between the RLFC core and the gypsum boards as it has strong adhesive properties. In the flexural strength test, all the test specimens possessed the same ultimate flexural strength which is 8 kN. However, sandwiched wall panel that utilized 9 mm gypsum board as the skin layer (G9) suffered the largest displacement of vertical deflection which is 6.69 mm in the mid-span among the other specimens. In the load bearing capacity test, G9 possessed the highest load bearing capacity which is 73.6 kN while suffering the largest displacement of lateral deflection which is 1.76 mm. All specimens failed under crushing mode in the load-bearing capacity test. The larger thicknesses of the sheathing materials in the specimens are stiffer to resist the effect of lateral and vertical deflection as well as mitigate the buckling effect. In the thermal conductivity test, G9 outperformed G12 and G16. The thickest RLFC core and lowest density of the gypsum board of G9 enabled it to be the best thermal insulator. In the flame exposure test, the surface conditions of all specimens were similar. The structural integrity as well as the connection between the RLFC core and the gypsum boards were not compromised. This study has proven that the gypsum board provided supreme fire protection and the RLFC core is feasible to be utilized as the inner core of the sandwiched wall panel system due to its high performance in thermal insulation.